Sentiment Analysis of Rapper Azealia Bank's Statement About "Indonesia is the World's Trash Can" on Social Media X (@azealiaslacewig) - Akbar Aldi Kautsar; Hasan Sazali; Afwan Syahril Manurung (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to analyze public sentiment towards rapper Azealia Banks' controversial statement calling Indonesia the "world's trash can" via her social media account X (@azealiaslacewig). This issue has caused various reactions from Indonesian people, especially social media users, which are reflected through comments, retweets, and replies that are spread massively. Using a sentiment analysis method based on qualitative and quantitative approaches, 500 tweets were collected and classified into three main categories: positive, negative, and neutral. The results showed that the majority of public responses were negative (72.4%), followed by neutral sentiment (19.2%) and positive (8.4%). Further analysis revealed that the high negative response was driven by a strong sense of digital nationalism and perceptions of insults to national identity. On the other hand, a small number of users showed positive or neutral responses by making the statement a reflection of environmental conditions and national waste management. These findings indicate that social media is an important arena for expressing collective emotions and attitudes towards global issues concerning national identity